LOCAL POWER AND MUHAMMADIYAH IN KOTAGEDE - Priyambudi Sulistiyanto (UIN Sunan Gunung Djati Bandung, 2014)
There has been a few studies on Kotagede with given focus on local architecture,cultural tourism, local politics and identity and the post-2006 earthquake inquiry butnone of them has a calibre of that of Nakamura’s.Overall, it is must be acknowledged that not much been written on this subject with a great depthsince Nakamura did field work in early 1970s and this left a big gap on thescholarship on Kotagede. This gap of knowledge is seriously needed to be filledbecause the findings of Nakamura’s study were basically based from the political andsocial changes occurred in Kotagede over past four decades.